LCF, HCF and VHCF life sensitivity to solution heat treatment of a third-generation Ni-based single crystal superalloy. (January 2020) - Bortoluci Ormastroni, Luciana Maria; Mataveli Suave, Lorena; Cervellon, Alice; Villechaise, Patrick; Cormier, Jonathan
Highlights: Different solution heat treatments have been applied to CMSX-4 Plus alloy to achieve different levels of metallurgical defects. VHCF life is mainly sensitive to the casting pore size, rather than the applied solution heat treatment. At fixed pore size, LCF life improves when the chemical homogeneity across the dendritic structure improves. Eutectics and incipient melting do not have any intrinsic detrimental impact on fatigue life of the alloy. Abstract: Fatigue life variability of a newly developed third-generation Ni-based single crystal superalloy resulting from different solution heat treatment procedures has been investigated in low cycle fatigue (T = 650 °C/Rσ = 0.05/f = 0.5 Hz), high cycle fatigue (T = 950 °C/Rσ = 0.05/f = 72 Hz), and very high cycle fatigue (T = 1, 000 °C/Rε = −1/f = 20 kHz). Special attention has been paid to the amount of γ/γ ′ eutectics, the dendritic chemical homogeneity, the casting pore size and, the presence of incipient melting areas. At fixed pore size, the chemical homogeneity across the dendritic structure is shown to be the main parameter controlling both low and high cycle fatigue through its effect on the yield stress at 650 °C, and oxidation resistance at 950 °C, respectively. While a greater variability is also obtained in very high cycle fatigue with a worse dendritic chemical homogeneity, the casting pore size remains the main parameter controlling fatigue life in the studied conditions. No detrimental impact of incipient melting on the fatigue life has been examined under these three testing conditions.